Megapolitical Cases before the Constitutional Court of Indonesia since 2004: An Empirical Study - Dressel, Björn; Inoue, Tomoo (Constitutional Review, 2018)
The Constitutional Court of Indonesia is considered one of Asia’s most activist courts. Here we investigate empirically possible determinants of the decisions of its judges over the period 2003–18. The findings are based on a unique data set of 80 high-profile political cases, complemented by data on the socio-biographic profiles of 26 judges who served during that period. Testing for common perceptions of the Constitutional Court since its inception, we first describe patterns in judicial decision-making across time and court composition before testing specifically for the impact of the judges’ professional backgrounds, presidential administrations, the influence of the Chief Justice, and cohort behaviour. The analysis finds declining dissent among justices on the bench over time and also provides evidence of strategic behaviour of justices at the ending of their own terms. But there is little statistical evidence that judicial behaviour has been affected by work background (except for those coming from the executive branch), appointment track or generation – hence suggesting that justices seem to retain more independence than the public seems to perceive. We then discuss the results in the context of Indonesia’s evolving constitutional democracy and look at the implications for comparative studies of judicial behaviour.